(untitled) (Bangladesh Veterinarian, 2013)
Probiotic organisms are live microorganisms thought to be beneficial to the host. To know the effect of probiotic supplemented food on haemato-biochemical parameters in mice, a total of 20 two-month-old Swiss Albino mice were randomly divided into four equal groups. Group A was control, fed commercial mouse pellets, and others were treated with 5 g (group B), 10 g (group C) and 20 g (group D) probiotics (curd), respectively, in mouse pellets for 45 days. Total erythrocyte count and haemoglobin concentration were significantly (P<0.01) higher in treated group than in controls. Total serum cholesterol, triglyceride, high density lipoprotein and low density lipoprotein values decreased significantly (P<0.01) in treated groups. Serum uric acid value was significantly higher (P<0.01) in treated groups. It is suggested that probiotics help improve haematology and lipid profile but not kidney function. DOI: http://dx.doi.org/10.3329/bvet.v30i1.16281 Bangl. vet. 2013. Vol. 30, No. 1, 20-24